Spirituality and Religion: A challenge to Near Eastern Studies - Nel, Philip Johannes (Journal for semitics, 2001)
The study of spirituality and religion has vastly increased in importance as a field of study within Near Eastern Studies (cum Semitics) compared to the status it enjoyed until quite recently. This shift of importance is a consequence of the broadening approach that can be detected in the traditional departments of Near Eastern Studies and Semitics and which is evidenced by their emphasis on cultural contextualisation and relevance to contemporary society. I